(untitled) (Bangladesh Journal of Dental Research & Education, 2014)
Infection is one of the most vital problems in health care service worldwide. A cross-sectional study was conducted to assess the standard and level of current infection control practice in the Dental clinics in Dhaka city. A total 110 purposively selected respondents participated in this study, most of them were from middle age group. Among them 68% were male and 32% were female. 62% respondents had graduate level education. By length of practice duration 53.6% had 5-10 years experience and 30.0% treat average 5-10 patients daily. Among the total respondents 77% of Dental surgeons were vaccinated against tetanus and hepatitis and 56% of respondents used to wash hands by water with soap. Within the total participating dentists 66% gave the history of habitual wearing of disposable gloves, 70.0% used disposable masks and 26.4% wore disposable clothes. The study also reported that, 44% of respondents usually washed clinical contact surface in the dental operatory by disinfectants and 33% of respondents cleaned the operatory surfaces after patient’s treatment by water and antiseptics. The study revealed that almost all dental surgeons used to use the disposable instruments & accessories in the clinic, 4I% clinicians used dettol in the clinic as disinfecting solution and 35.8% respondents sterilized their instruments by autoclave. The research work found that 73.6% respondents mentioned to clean the prosthodontic instruments by detergent wash, 68.2% mentioned to use glass bid sterilizer to sterilize the endodontic instruments and 68% reported about surgical instruments to sterilize by autoclave just after cleaning with detergent wash without using the disinfectant solutions. This study also found that 77.3% disposed the sharp instruments in plastic container, 20.9% maintained color code during disposal of medical wastes and 58.2% respondents used to dispose medical wastes with general wastes. The study revealed that 69.1% cleaned the non patient area by mop and detergent only. According to the agreements of the respondent’s 71% reported that very few of the patients complained about secondary infection, 81% gave no history of cross infection after receiving operative procedure. 50.9% respondents mentioned about participation in training session on infection control procedure at least once in their lifetime. Policy on immunization should be developed for Dental health workers and farther studies involving larger sample size is recommended. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20252 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 65-69